1978
DOI: 10.1007/bf00165504
|View full text |Cite
|
Sign up to set email alerts
|

Kelvin-Helmholtz waves observed by aircraft at different stages of their life-cycle in a low-level inversion

Abstract: Wave-like motions within a low-level inversion capping a morning mixed layer are studied with two instrumented aircraft, one of which is equipped with a fast-response air sensing probe. Kelvin-Helmholtz waves and their different stages of development (growth, overturning and decay) are identified by means of spectral analyses of temperature and wind component records. By analysing energy conversion rate cospectra, it is found that mechanical production terms and buoyancy production terms, respectively positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1983
1983
1983
1983

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…It is well known that the capping stable layer is frequently dynamically unstable so that instability waves might develop there (Gossard and Hooke, 1975). For example, Mascart et al (1978) have investigated such wave motions observed during the Limagne experiment. Random gravity wave fields may also be excited in the stable layer by bombarding thermals (Townsend, 1966;Deardortf et al, 1969).…”
Section: Height Variation Of Zmentioning
confidence: 99%
“…It is well known that the capping stable layer is frequently dynamically unstable so that instability waves might develop there (Gossard and Hooke, 1975). For example, Mascart et al (1978) have investigated such wave motions observed during the Limagne experiment. Random gravity wave fields may also be excited in the stable layer by bombarding thermals (Townsend, 1966;Deardortf et al, 1969).…”
Section: Height Variation Of Zmentioning
confidence: 99%